Taphonomy of fossils mollusks of Bauru Group (Late Cretaceous, Bauru Basin), in Monte Alto municipality region, São Paulo, Brazil - Ghilardi, Renato Pirani; D’Ágosta, Fernando César Paiva; Alves, Kléber; Campos, Antonio Celso de Arruda (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
Bivalves mollusks fossils of Bauru Group (Late Cretaceous, Bauru Basin) deposited in scientific collections and collected in outcrops from Monte Alto municipality, São Paulo, are analyzed in their taphonomy. The preservation of recrystallized individual in carbonatic matrix indicates substrate remobilization by unidirectional energetic event in fluvial discharge. The specimens with conjugated valves possess internal sediment similar to the external indicating low exposition to Taphonomical Active Zone, suggesting a bioclastic low time-averaging. The truncate and fragmented posterior portion of specimens from scientific collections is probably related to the incapacity of the taxa to reburrowing the substrate in drowning periods. Both taphonomic patterns corroborate evidences of a fluvial paleoenvironment in the Bauru Group.